The evolution of 7th graders scientific explanations in project-based classrooms - Novak, Ann M. (Curtin University, 2014)
This thesis documents the process of fifty-eight, 7th grade students constructing one scientific explanation, through four iterations, as new evidence was obtained. Students delved deeply into core ideas and explained causal relationships. This “evolving explanation” shows promise in supporting students to develop integrated understanding through building a more sophisticated explanation over time. Utilizing a time series research design and mixed methods analyses results indicate eight of the nine research questions explored showed statistically significant effects.